Osteoarthritis and degenerative joint disease: local treatment optionsupdate - Palmieri, B.; Lodi, D.; Capone, S. (Acta Biomedica Atenei Parmensis, 2010)
This review describes intra-articular drugs therapy of arthritis and degenerative joint disease) with a range of old and recent molecules with specific focus on hyaluronic acid. HA is a cartilage matrix basic component secreted by chondrocytes: it prevents cartilage degradation by a complex interpherence between metalloproteinases, pain mediators and cells. Local injections of HA improve functional activity and pain management, particularly when it is combined with other selected drugs.